Particle Flow Code Simulation of the Characteristics of Crack Evolution in Rock-Like Materials with Bent Cracks - Zhanguo Ma; Shixing Cheng; Peng Gong; Jun Hu; Yongheng Chen (Geofluids)
The distribution and propagation of rock cracks have a significant impact on geotechnical engineering. Taking rock-like materials with bent cracks as the research object, the particle flow code in two dimensions numerical simulation method was used to study the impact of the bend number on rock-like materials strength and crack evolution. According to the results, when the bend number was 1, 3, and 7, the strength of the specimens gradually increased; the elasticity modulus did not change significantly with the crack bend number. Uniaxial compression generated tensile cracks in all the specimens with bent cracks, but in terms of failure mode, the specimens with 0 bend tended to suffer penetrating failure along the fracture strike, while the specimens with 1, 3, and 7 bend tended to suffer penetrating failure along the diagonal direction. Both the fractal dimension and bend number were positively correlated with strain; with the gradual increase of the stress percentage, the damage variable of the specimens gradually increased at a growing rate. The research results provide a reference for predicting the stability of the underground engineering surrounding rocks containing bent cracks.